Simulations of dispersion and deposition of coarse particulate matter - Cionco, Rodolfo (2009)
In order to study the dispersion and deposition of coarse anthropogenic particulate matter (PMc, aerodynamic diameters> 10 mm), a FORTRAN simulator based on the numerical integrator of Bulirsch and Stoer has been developed. It calculates trajectories of particles of several shapes released into the atmosphere under very general conditions. This first version, fully three-dimensional, models the meteorology under neutral stability conditions. The simulations of such pollutants are also important because the standard software (usually originating in the United States Environmental Protection Agency-EPA-) describe only the behavior of PM10 (diameter less than 10 mm). Bulirsch and Stoer integrator of widespread use in astrophysics, is also very fast and accurate for this type of simulations. We present 2D and 3D trajectories in physical space and discuss the final deposition in function of various parameters. PMc simulations results in the range of 50-100 mm and densities of 5.5 g cm-3 emitted from chimneys, indicate that for the purpose of deposition, the emission velocities are not as important as wind speed and the shape of the particles. For densities less than 2 g cm-3, the lack of consideration of buoyancy introduces important changes in the distribution of deposited PMc.